UPAYA KEPALA SEKOLAH MENINGKATKAN DISIPLIN KEHADIRAN GURU MENGAJAR MELALUI PENERAPAN REWARD AND PUNISHMENT DI SMP NEGERI 2 BOGOR - Ema Mustikawati (Journal of Social Studies, Arts and Humanities (JSSAH), 2021)
THE PRINCIPAL'S EFFORTS TO IMPROVE THE DISCIPLINE OF TEACHING TEACHER ATTENDANCE THROUGH THE APPLICATION OF REWARD AND PUNISHMENT IN JUNIOR HIGH SCHOOLS (SMP NEGERI 2 KOTA BOGOR)The presence of teachers in teaching classes at Junior High Schools (SMP Negeri 2 Kota Bogor) is the problem behind conducting school action research. Improving the quality of learning in schools is very dependent on several factors, one of which is the discipline of teachers in teaching. This research aims to; (1) knowing the application of reward and punishment can improve attendance discipline in teaching, (2) describing the process of increasing class attendance discipline after applying reward and punishment, (3) measuring the magnitude of the increase in teacher attendance discipline in teaching in class after applying reward and punishment. This type of research is School Action Research with two cycles. Each cycle consists of planning, implementing, observing and reflecting. The results of this study are the percentage of teacher delays in class less than 10 minutes obtained in the pre-cycle of 10% increased to 50% in the first cycle, and increased again to 80% in the second cycle. This has exceeded the specified target, which is 80% of teachers are not late for class more than 10 minutes. While the percentage of teachers leaving the class according to the schedule in the pre-cycle is 0%, which means 10 teachers who are the subjects of the study left the class earlier than the specified schedule, in the first cycle there was an increase of 50% of teachers increasing the discipline of attendance in teaching by leaving the class on schedule, and increased again to 100% in cycle II. This has reached the specified target of 100% of teachers leaving the class according to the lesson schedule. Based on the results of these studies, it can be concluded that the application of reward and punishment to teachers can improve the discipline of teacher attendance in junior high schools (SMP Negeri 2 Kota Bogor).